DESIGNING ICT COMPETENCES-INTEGRATED ASSESSMENT INSTRUMENTS OF PRACTICAL KEY TEACHING COMPETENCES FOR ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Made Gede Dwi Susantha S.; Sri Sumarni (IJLECR (International Journal of Language Education and Cultural Review), 2019)
The rapid development of information and communication technology (ICT) in this 21st century arises a new major challenge in education. 21st century learning challenges require the assessment instrument to be integrated with the ICT competences which is not yet accomplished by the existing assessment instrument. This study aims to design ICT competence-integrated assessment instruments of practical key teaching competences courses. This research adapted Design and Development Research (DDR). The used of DDR stages are need analyzing, designing. prototype and evaluation. The data were taken from the existing assessment instruments from seven different universities in Indonesia. The result of the research shows that first, the existing assessment instruments make use of ICT in extent of technology literacy where the ICT competences indicators that mostly used were using word processing software by following standard conventions, using ICT resources to enhance their productivity and download resources from websites. Second, based on the need analysis the researcher designed the procedures of integrating ICT competences into table of specification of practical key teaching competences. Third, the researcher designed the table of specifications of practical key teaching competences course namely, lesson course planning, Instruction Management and Monitoring and Teaching Practice. Fourth the researcher designed the ICT competences- integrated assessment instrument test of practical key teaching competences course namely, lesson course planning, Instruction Management and Monitoring and Teaching Practice. The last, the researcher designed the ICT competences-integrated assessment instrument non-test of practical key teaching competences course namely, lesson course planning, Instruction Management and Monitoring and Teaching Practice.